Manajemen Kurikulum Berbasis Etnosains untuk Pewarisan Budaya Berkelanjutan - Mahfud, Muhammad; Rudianto, Rahmat (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research aims to find an ethnoscience-based curriculum management model for sustainable cultural inheritance. This research is included in the descriptive research category with a qualitative approach. Data collection methods were carried out by means of Focus Group Discussions, in-depth interviews and also documentation. The research results show that ethnoscience-based curriculum management is structured through four stages, namely planning, organizing, actuating, and controlling. In implementing an ethnoscience-based curriculum, you must pay attention to the principles of integration, relevance, efficiency, effectiveness and flexibility. The learning process in an ethnoscience-based curriculum uses a contextual approach by presenting learning content in a context that is relevant to students based on their cultural and social realities. The form of learning is active learning. The forms of strategy that can be used by educators are group discussions, project based learning (PjBL), problem based learning (PBL), discovery learning, inquiry learning, and presentations to build in-depth understanding. Apart from that, cultural reflection can also be done to build students' critical reasoning.